2011
DOI: 10.1103/physreva.83.062708
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of dielectronic recombination of Sn12+ions

Abstract: Theoretical calculations have been made for the dielectronic recombination (DR) rate coefficients of Sn 12+ ion using a relativistic flexible atomic code with configuration interaction. Comparison of the rate coefficients for 4s, 4p, and 4d subshell excitation shows that while the 4p subshell excitation dominates over the whole temperature region, 4d subshell excitation at low temperature and 4s subshell excitation at high temperature cannot be neglected. In order to facilitate simple applications, the calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…With respect to excitations from the 3l subshells, it is found that the DR rate coefficients for 3d subshell excitation are the largest and that the partial rate coefficients decrease with the decreasing l quantum number. This characteristics is similar to the case of Sn 12+ [77] and Pd 19+ [80] ions. For electron temperatures lower than 100 eV, excitations from the 3l subshells are much less significant than from the 4l subshells, and thus, the contributions to total DR rate coefficients can be neglected.…”
Section: Dielectronic Recombination Rate Coefficientssupporting
confidence: 80%
See 1 more Smart Citation
“…With respect to excitations from the 3l subshells, it is found that the DR rate coefficients for 3d subshell excitation are the largest and that the partial rate coefficients decrease with the decreasing l quantum number. This characteristics is similar to the case of Sn 12+ [77] and Pd 19+ [80] ions. For electron temperatures lower than 100 eV, excitations from the 3l subshells are much less significant than from the 4l subshells, and thus, the contributions to total DR rate coefficients can be neglected.…”
Section: Dielectronic Recombination Rate Coefficientssupporting
confidence: 80%
“…The excitations from K and L shells are not taken into account in the present calculations due to their negligible contribution to total DR rate coefficients [77]. The contributions from higher-n states are extrapolated up to n = 1000 using the empirical (n ) −3 scaling [78].…”
Section: Dielectronic Recombination Rate Coefficientsmentioning
confidence: 99%
“…Moreover, from other studies it can be inferred that the influence of 3d-core excitation is much smaller than for the 4s shell [33]. Therefore, the contributions from 4s and 3d complexes can be essentially ignored in the present calculations.…”
Section: B the Partial Dr Rate Coefficientsmentioning
confidence: 79%
“…The dominance of these transitions in both Xe and Sn spectra would seem to imply that the upper doubly excited states are selectively populated in the charge exchange process either by a transfer excitation process in which electron capture is accompanied by the excitation of a 4p or 4d electron or a TI process in which the projectile ion autoionizes to a doubly excited state. It has been shown that in low energy electron scattering that the dielectronic recombination is greatly enhanced because of the large density of states resulting from open n = 4 subshells which leads to the dielectronic recombination rate exceeding that for radiative recombination by almost two orders of magnitude [26][27][28]. The agreement between calculated and experimental spectra decreases with increasing charge.…”
Section: Discussionmentioning
confidence: 97%